SEEDS OF TOMORROW: IMPLEMENTING INTENTIONAL AND RESPONSIVE IN CHILDCARE CENTRES TO REFLECT MODERN PARENTAL ASPIRATIONS - FATIMAH NABIHAH MUSTAFA; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Early childhood education is a critical stage that determines children's life trajectory. In Malaysia, childcare centers TASKA play a crucial role in establishing disciplined and nurturing learning environments for infants and toddlers. This library research explores how Malaysian TASKA apply teaching and learning approaches aligned with the dreams of modern parents. The study focuses on four essential dimensions: Intentional and Responsive Teaching, Play-Based and Child-Centered Learning, Family Engagement and Socio-Emotional Support, and Professional Development and Systemic Support. Using secondary data from academic journals, government documents, and online databases, this research outlines how these practices are pursued in child care centers and how they affect holistic child development. The study shows that modern parents expect child care centers not only to offer protection and care but to instill quality education that enhances children's mental, social, and emotional capabilities. The report concludes with policy, parental, and teacher recommendations to further enhance Malaysia's early childhood education quality.